2018
DOI: 10.1111/jvim.15064
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potential serum biomarkers of hepatic fibrosis and necroinflammatory activity in dogs with liver disease

Abstract: BackgroundSerum interleukin 6 (IL‐6), chemokine ligand 2 (CCL2), C‐reactive protein (CRP), and the ratio of aspartate transaminase to alanine transaminase (AST:ALT) have been correlated with fibrosis and necroinflammatory activity in humans with various hepatopathies.Hypothesis/ObjectivesTo determine whether increases in serum IL‐6, CCL2, CRP, or AST:ALT were associated with moderate to severe fibrosis or necroinflammatory activity in dogs with various hepatopathies.AnimalsForty‐four client‐owned dogs with cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 56 publications
3
30
0
1
Order By: Relevance
“…In contrast, patients affected by severe OSA had different levels of liver serum biomarkers 11 and elastography studies has shown excellent correlation between the SWV values and biochemical predictors of liver fibrosis (ratio AST/ALT) and between levels of liver biomarkers individually (ALT, AST, GGT and total bilirubin) 30,58 . Whereas, the ratio AST/ALT has no significant correlation to liver fibrosis in dogs and actually has an overlap of values between healthy and affected dogs 24 and, therefore, the ALT and AST enzymatic activities were evaluated individually in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, patients affected by severe OSA had different levels of liver serum biomarkers 11 and elastography studies has shown excellent correlation between the SWV values and biochemical predictors of liver fibrosis (ratio AST/ALT) and between levels of liver biomarkers individually (ALT, AST, GGT and total bilirubin) 30,58 . Whereas, the ratio AST/ALT has no significant correlation to liver fibrosis in dogs and actually has an overlap of values between healthy and affected dogs 24 and, therefore, the ALT and AST enzymatic activities were evaluated individually in this study.…”
Section: Discussionmentioning
confidence: 99%
“…the most important prognostic factor related to NAFLD 19 . The liver injury and fibrosis are also associated with concomitant portal hypertension 20 that can lead to spleen alterations 21,22 and changes in serum biomarkers 23,24 .…”
mentioning
confidence: 99%
“…The H&E‐stained slides were scored for necroinflammatory activity and fibrosis (Table ). A validated scoring system for hepatopathology in dogs does not exist, and the scoring system used herein was derived from the same sources used in previous veterinary publications . It closely resembles a scoring system proposed by the World Small Animal Veterinary Association Liver Standardization Group with the exception that centrilobular inflammation was treated as a distinct category, given the classic pattern of copper accumulation and inflammation in CAH .…”
Section: Methodsmentioning
confidence: 99%
“…A validated scoring system for hepatopathology in dogs does not exist, and the scoring system used herein was derived from the same sources used in previous veterinary publications. 22,[34][35][36] It closely resembles a scoring system proposed by the World Small Animal Veterinary Association Liver Standardization Group with the exception that centrilobular inflammation was treated as a distinct category, given the classic pattern of copper accumulation and inflammation in CAH. 31 Briefly, scores were assigned for the severity of fibrosis (range, F0-F4), centrilobular inflammation (range, C0-C3), portal inflammation (range, P0-P3), lobular necrosis (range, LN0-LN2), and piecemeal necrosis (range, PMN0-PMN3).…”
Section: Hepatic Histopathology and Quantitative Mineral Determinatmentioning
confidence: 99%
“…Inflammatory markers such as C-reactive protein12 and haptoglobin13 have previously been investigated in chronic hepatopathies. However, there is a paucity of data evaluating the utilisation of routinely available haematological variables in prognosticating dogs with chronic hepatitis.…”
Section: Introductionmentioning
confidence: 99%